2020
DOI: 10.3389/fimmu.2019.03078
|View full text |Cite
|
Sign up to set email alerts
|

Factor VIII: Perspectives on Immunogenicity and Tolerogenic Strategies

Abstract: Therapeutic treatment of bleeds with FVIII can lead to an antibody response that effectively inhibits its function. Herein, we review the factors that contribute to this immunogenicity and possible ways to overcome it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 92 publications
0
13
0
Order By: Relevance
“…3 ), and subsequently we used the trained classifier algorithms to predict the chromogenic activities of hypothetical alanine mutations at residues from the A1, A3 and C1 domains (Supplementary Table 2 ). Interestingly, we found that amino acids at binding sites were not particularly central, creating the tempting hypothesis that they can be substituted in therapeutic proteins to increase the FVIII binding affinity and to modulate its immunogenic profile 61 .…”
Section: Discussionmentioning
confidence: 99%
“…3 ), and subsequently we used the trained classifier algorithms to predict the chromogenic activities of hypothetical alanine mutations at residues from the A1, A3 and C1 domains (Supplementary Table 2 ). Interestingly, we found that amino acids at binding sites were not particularly central, creating the tempting hypothesis that they can be substituted in therapeutic proteins to increase the FVIII binding affinity and to modulate its immunogenic profile 61 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the generation of neutralizing antibodies renders treatment ineffective in up to 30% of the severe patients. 1 , 2 Emicizumab is a humanized bispecific antibody that binds simultaneously to activated factor IX (FIXa) and factor X (FX), thereby mimicking the cofactor function of activated factor VIII (FVIIIa), even in the presence of FVIII inhibitors. 3 , 4 Once-weekly subcutaneous administration of emicizumab markedly decreased the bleeding rate in patients who had hemophilia A with or without FVIII inhibitors.…”
mentioning
confidence: 99%
“…Challenges with the incorporation of these therapeutics into clinical care include the lack of standardisation of coagulation assays and the limited long‐term safety data with regard to the theoretical risk of PEG exposure for routine prophylaxis indications 16,17 . Data on EHL factor concentrates remains limited in the paediatric population, particularly in previously untreated patients (PUPs), with a preclinical model supporting potential for increased induction of tolerance 18 . Table III 1–8 includes key data from studies in children, with even more sparse data on EHL product use in PUPs summarised in Table IV.…”
Section: Factor Concentratesmentioning
confidence: 99%
“…16,17 Data on EHL factor concentrates remains limited in the paediatric population, particularly in previously untreated patients (PUPs), with a preclinical model supporting potential for increased induction of tolerance. 18 Table III [1][2][3][4][5][6][7][8] includes key data from studies in children, with even more sparse data on EHL product use in PUPs summarised in Table IV.…”
mentioning
confidence: 99%